Combined effects of graphene oxide and zinc oxide nanoparticle on human A549 cells: bioavailability, toxicity and mechanisms. Issue 2 (24th January 2019) - Wu, Bing; Wu, Jialu; Liu, Su; Shen, Zhuoyan; Chen, Ling; Zhang, Xu-Xiang; Ren, Hong-qiang
Abstract : The toxic effects of multinanomaterial systems are receiving more attention due to their release of various nanomaterials. Abstract : The toxic effects of multinanomaterial systems are receiving more attention due to their release of various nanomaterials. However, the knowledge of the influence of two-dimensional carbon nanomaterials on the bioavailability and combined toxicity of metal oxide nanoparticles in human cells is limited. In this study, we analyzed the interaction and combined toxicity of graphene oxide (GO) and zinc oxide nanoparticles (nano-ZnO) in the human lung carcinoma epithelial A549 cell line. The results showed that GO (1, 5 and 10 mg L −1 ) did not change the precipitation and Zn 2+ release of nano-ZnO in the cell culture medium and had low adsorption capability to Zn 2+ . However, GO could reduce the bioavailability and toxicity of nano-ZnO in cell viability, oxidative stress, mitochondrial depolarization, and membrane damage. The metabolomics analysis showed that exposure to nano-ZnO alone and coexposure to both nanomaterials significantly changed the metabolome profiles and had higher similar impacts on tricarboxylic acid cycle, glutathione synthesis, nucleoside synthesis and lipid metabolism. However, GO reduced the impact of nano-ZnO upon fold changes of the most altered metabolites. Furthermore, in this study, we found that GO increased the toxicity of Zn 2+, which differed from the effects of GO on nano-ZnO. This difference might be due to different modes of action, such that GO decreased the uptake of nano-ZnO, but inhibited the efflux of Zn 2+ in cells. The results of this study provided insights into the combined toxicity evaluation of GO and metal oxide nanoparticles.